Janez Trdina in Paskoje Antun Kazali - Pogačnik, Jože (Slavistična revija, 1997)
The paper discusses the biographic, psychological, and literary ties between J. Trdina and the Croatin writer P. A. Kazali. The period in question is about five years of life together at Rijeka Gymnasium (between 1961 and 1866); in these years both close friends formed similar views of the society and literature, which can be deciphered from their literary work ot those and later years.
Keywords: biografije; Croatia; Hrvaška; hrvaški pisatelji; Kazali, Paskoje Antun, 1815-1894; kulturna zgodovina; Slovenia; Slovenija; slovenski pisatelji; slovensko-hrvaški stiki; Trdina, Janez, 1830-1905